Extensible website solutions: instant creation and publishing of custom academic website / Zuraini Ibrahim - Ibrahim, Zuraini (2004)
Internet is very important source of facility that helped people in the world to get information in conducting business and campus activities, banking transactions, to access sources of entertainment and to shop for goods and services. It has been used broadly by the societies or individuals and becomes one of the new technologies towards the year 2000. Website is one of the parts of the internet. Today's, instant website is very new and yet becoming very popular among business organization and universities around the world to publish their information. Instant website can be developed and deployed instantly by almost anyone using website generator, without having to know any programming languages, computer design skills or database architecture. This paper presents the study on develop and publishing an instant academic website which can be customized by lecturer in proposing an instant website for lecturer in FTMSK. The Extensible Website Solutions: Instant Creation and Publishing of Custom Academic Website will be demonstrated through the 'FTMSK WebVille' project. It enables lecturers and students from a faculty to interact each other in the website. As a web based system, the Iterative Development Methodology is chosen. This website contains information of the lecturer such as name, room number and telephone number, lecture notes, calendar, user poll, weblog, news (RSS) and so on. The objective of this system is to create a dynamic template that can generate all the lecturer's website and to facilitate the generation of a lecturer's web page by automating the code generation process where the lecturers no need to have any web programming languages and only need to input their relevant information into the template. There are the combinations of DHTML, PHP, JavaScript, VBScript, MySQL (as a database) and Flash plug-ins, which are selected to design an interactive interface and make it function properly.